Locally applied simvastatin promotes bone formation in a rat model of spinal fusion. Issue 9 (14th December 2016) - Ishihara, Toshinobu; Miyazaki, Masashi; Notani, Naoki; Kanezaki, Shozo; Kawano, Masanori; Tsumura, Hiroshi
ABSTRACT: Simvastatin, an inexpensive lipid‐lowering drug widely used to prevent cardiovascular disorders, is known to increase osteoblastic activity, inhibit osteoclastic activity, and stimulate osteoblastic production of bone morphogenetic protein 2. Furthermore, local simvastatin application increased bone formation in animal models of fracture or bone defects. We investigated the effect of locally applied simvastatin in a rat model of spinal fusion. We performed posterolateral lumbar fusion surgery with iliac crest autograft in 36 rats divided into group I ( n  = 17; implanted with a gelatin scaffold) and group II ( n  = 19; implanted with a gelatin scaffold infused with 0.5 mg simvastatin). The rats were euthanized at 6 or 12 weeks postoperatively, and the spines were explanted and assessed. The fusion rates in group II (16.7%: 6 weeks, 30%: 12 weeks) were considerably higher than those in groups I (0%: 6 weeks, 0%: 12 weeks). The 6‐ and 12‐week radiographic scores were significantly higher in group II than in group I. High‐resolution micro‐computerized tomography revealed that the tissue and bone volumes of the callus tended to be higher in group II than in group I. Histologic analysis of the spines explanted after 12 weeks demonstrated new bone formation between the transverse processes in group II, but thicker and wider individual trabeculae with fibrotic tissue and muscle fiber between the transverse processes in group I. Locally applied simvastatin was efficacious in accelerating bone formation in our rat model of spinal fusion, supporting its potential clinical application as a promoter of bone morphogenesis in spinal fusion. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1942–1948, 2017.